The 'first business of government': The land granting administration of Upper Canada. - Moorman, David T. (University of Ottawa (Canada), 1998)
When the Loyalist refugees fleeing the American revolution in the 1780's arrived in what would become the province of Upper Canada, the colonial government faced a new and unwelcomed situation. Colonial officials in both London and Quebec abandoned their plans for the expansion of the French colony and the preservation of an extensive western Native reservation in favour of a British-style settlement, complete with a balanced constitution, common law, and free and soccage land tenure. The first business faced by this new conservative-minded, loyal government was the distribution of land. In conducting this business the Imperial government, and its officers in Upper Canada, constructed an administration that mixed inherited continuities with innovation. Through the desire for efficiency and accountability, this administration was slowly transformed from a quasi-feudal to a modern bureaucratic system. Many of the decisions and actions of the colonial administrators proved effective and far-sighted, others were much less so. In the end, however, the government was neither corrupt nor incompetent, and, by the 1830's, they succeed in accomplishing the principal goal of land granting; the broad distribution of land to industrious settlers loyal to the British monarchy. The structures through which this was accomplished became the framework of Canada's modern bureaucracy.
Keywords: History, Canadian.